Effect of Postmortem Aging Period on the Meat Quality, Sensory Properties and Total Bacterial Count of Western Baggara Bulls Meat - Nour, Ikhlas Ahmed; Babiker, Salih Ahmed (Journal of Veterinary Medicine and Animal Production, 2021)
A study was conducted to investigate the effect of postmortem aging period (1, 5, 10, and 15 days) on meat quality of bovine muscles, Longissimus dorsi, Semimembranosus and Semitendinosus, held at 2°C. Fourteen western Baggara bulls were used. The hindquarters were immediately chilled at 2°C for 24 hours, Longissimus dorsi, Semimembranosus and Semitendinosus were cold deboned, each one was divided into four parts and aged immediately after deboning for 1, 5, 10 and 15 days at 2°C, chemical composition, bacterial load and muscle eating quality were determined. Extractable myofibrillar proteins, non-protein nitrogen and water holding capacity were increased (P<0.001), while the extractable sarcoplasmic proteins significantly (P≤0.001) decreased; cooking loss and colour rating scores decreased and tenderness increased numerically with increasing aging period to 15 days. Increasing aging period from 5 to 15 days resulted in low flavour rating and increased juiciness but non-significantly for the three muscles studied. The total bacterial counts values increased slightly with increasing the aging period but the differences between days 1 (control), 5 and 10 were not significant (P>0.05) it was only significant between day 15 of aging and the other aging times for all the muscles. SDS polyacrylamide gel electrophoresis revealed a gradual decrease and disappearance of the troponin-T and a built up of a 30 kd component seems to be the major changes during postmortem aging. Complete disappearance of toponin-T and appearance of a 30 kd component at day 10 of aging and continue to be observed at day 15. Aging of Baggara bulls carcasses for 10 days at 2°C is recommended.